1985
DOI: 10.1093/jn/115.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Growth in Iron-Deficient Rats: Effect of Pre- and Postweaning Iron Repletion

Abstract: Effects of iron deficiency and repletion pre- and postweaning on cell growth in young rats were studied. Pregnant dams were fed 6 or 250 ppm iron. On d 2 of lactation, half of the dams in each group were fed the opposite diet. On d 17, cell growth in the crossed-over groups was similar to controls showing that cellular development is impaired only when the iron deficiency is present during gestation and lactation. In a second experiment pup littermates of dams fed 6 (D), 12 (M) and 250 (C) ppm iron were weaned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Fecal moisture content, expressed inversely as dry matter content, revealed that ID pigs had a 50% more moisture in feces compared with CONT pigs, thus it is possible that diarrhea was present, possibly associated with the higher levels of Escherichia / Shigella detected in ID pigs. It is also well-established that ID and IDA can lead to diminished immune function and higher susceptibility to pathogens (50, 51). Despite being iron-requiring bacteria, the greater susceptibility of ID pigs to illness may also contribute with the higher amount of Escherichia/Shigella observed.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal moisture content, expressed inversely as dry matter content, revealed that ID pigs had a 50% more moisture in feces compared with CONT pigs, thus it is possible that diarrhea was present, possibly associated with the higher levels of Escherichia / Shigella detected in ID pigs. It is also well-established that ID and IDA can lead to diminished immune function and higher susceptibility to pathogens (50, 51). Despite being iron-requiring bacteria, the greater susceptibility of ID pigs to illness may also contribute with the higher amount of Escherichia/Shigella observed.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of iron status conducted in developing countries have used biomarkers of inflammation to determine the influence of this inflammation on markers of iron-status [ 27 29 ]. SF is an acute phase reactant which is elevated during inflammation [ 30 ]. These associations could be a result of the weight differences observed to be higher in girls.…”
Section: Discussionmentioning
confidence: 99%
“…Increased haeme concentrations may subsequently improve iron utilization because haeme iron is utilized much better than nonhaeme iron (Morris, 1987). Kochanowski and Sherman (1985) noted that iron nutrition can affect development of cell-mediated immunity. In addition, other functions such as iron involvement in proper enzymatic function of immune cells and regulation of cytokine production were also reviewed by Beard (2001).…”
Section: Discussionmentioning
confidence: 99%